The Relationship Between Onset Time and Outcome Patients Intra Cerebral Ganglia Basalis EC Stroke Hemorrhagic Operations at Dr. Mohammad Hoesin General Hospital Palembang - Ditto Ruldifar Pribadi; Anugrah Onie; Theodorus (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2021)
Background: Spontaneous intracerebral hemorrhage is the second most common stroke subtype defined as non-traumatic hemorrhage to the brain parenchyma, which can extend to the ventricles and into the subarachnoid space. Advances in innovations in the field of surgical intervention compared to conservative therapy are more beneficial in preventing disability in patients. The surgical methods that are often used in nontraumatic intra cerebral bleeding interventions are craniotomy and craniectomy. Many factors influence postoperative patient outcome. The level of patient awareness, the extent of the hematoma are the main predictive factors for patient outcome. Glasgow Outcome Scale is often used to measure the outcome of intracranial bleeding patient care. Methods: The study is a case series studies which was conducted by tracing 70 medical records of patients with intra-cerebral ganglia basal hemorrhage due to stroke hemorrhagic who had met the study inclusion criteria from January 2018 to December 2020 who were operated on at the Neurosurgery Installation of RSUP Dr. Mohammad Hoesin Palembang. Results: The mean ICH age in the study was 40 - 60 years (54.23 ± 13.09), male gender were 41 samples (58.6%), mean GCS was 10.93 ± 2.48 (3-15), pressure systolic blood 171.33 ± 24.09 (120 - 240), diastolic blood pressure 98.8 ± 13.46 (70 - 140), most patients ICH with a history of hypertension 68 people (97.1%), 60 people (85.7%) without a history of DM, 57.1% with craniotomy, 59 people with a bleeding volume of 30-60 cc (84.3%), surgery onset ≥ 8 hours (68.6%), uncal herniation (57.1%). Craniotomy and craniectomy were not significantly associated with the prognostic assessment of GOS on ICH (p value = 0.502). Uncal herniation was significantly associated with the incidence of ICH (p value = 0.000). The correlation was strong between time of onset and patient prognosis (p 0.000). Conclusion: There was a significant relationship between onset time and patient outcomes, meaning that the correlation between onset time and patient outcomes was quite strong. The longer the onset time, the more likely it is to have a bad outcome (GOS score 4-5), whereas the faster the onset time, the more likely it is to have a good outcome (GOS score 1-3).